2020
DOI: 10.5005/jp-journals-10071-23563
|View full text |Cite
|
Sign up to set email alerts
|

Immature Granulocyte Count and Percentage as New Predictors of Mortality in Patients with Upper Gastrointestinal Bleeding

Abstract: A bstract Aims Early identification of patients at risk of adverse outcomes may increase the survival rates in patients with upper gastrointestinal bleeding (UGIB), but this can be difficult to predict in emergencies. The aim of the study is to evaluate immature granulocyte (IG), which can be obtained from simple hemogram tests in patients with UGIB, in terms of clinical use and as a mortality marker. Materials and methods The patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Moreover, its presence has been reported to be predictive of mortality in relation to many gastrointestinal diseases. 5,6,26 No studies in the literature have yet examined the correlation between IG and AIS. Park et al reported that IG might be a marker for mortality due to sepsis, and its sensitivity for mortality in their study was found to be 70%; specificity was found to be 78%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its presence has been reported to be predictive of mortality in relation to many gastrointestinal diseases. 5,6,26 No studies in the literature have yet examined the correlation between IG and AIS. Park et al reported that IG might be a marker for mortality due to sepsis, and its sensitivity for mortality in their study was found to be 70%; specificity was found to be 78%.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic and predictive role of IGs has been shown in relation to many diseases. 5,6 However, the role of IGs in patients with AIS has not been clearly revealed until now.…”
Section: Introductionmentioning
confidence: 99%
“…Immature granulocyte, one of these new inflammatory markers, is an indicator of increased myeloid cell production and it has been shown to increase in inflammatory conditions [7,8]. In recent studies in the literature, it has been shown that immature granulocyte count (IGC) and immature granulocyte percentage (IG%) are useful as inflammatory markers in many diseases such as acute pancreatitis accompanied by inflammation, acute appendicitis, acute gastrointestinal hemorrhage and intracerebral hemorrhage [9][10][11][12]. There is no study yet showing the predictivity of IGC and IG% in the diagnosis of AC.…”
Section: Introductionmentioning
confidence: 99%
“…The immature granulocytes (IG) count, which is a practical marker of local and systemic inflammation, can be quickly and easily obtained using a complete blood count (CBC) by means of recent technological advances such as automated blood cell analysers. The IG count can reflect the fraction of circulating IG without demanding extra costs or time [ 7 - 9 ] . A literature review has shown that only a few studies have investigated the association between the IG count and the severity of STEMI.…”
Section: Introductionmentioning
confidence: 99%